Дослідження сучасних підходів до визначення тривалості cтадій життєвого циклу промислового підприємства - Гончаренко, Т.П. (Культура народов Причерноморья, 2013)
В статті продемонстровані результати дослідження, сучасних на даному етапі розвитку
економічної науки, підходів до визначення тривалості стадій життєвого циклу промислового
підприємства. Виявлені та систематизовані специфічні особливості стадій життєвого циклу для
промислових підприємств. Проведений порівняльний аналіз існуючих підходів до виявлення етапів
життєвого циклу підприємства та за умов наявності наукових розробок з визначення дії кожного з них,
були з’ясовані розходження у загальному періоді діяльності підприємства. В статье продемонстрированы результаты исследования, современных на данном этапе
развития экономической науки, подходы к определению длительности стадий жизненного цикла
промышленного предприятия. Выявлены и систематизированы специфические особенности стадий
жизненного цикла для промышленных предприятий. Проведен сравнительный анализ существующих
подходов к выделению этапов жизненного цикла предприятия и при наличии научных разработок по
определению времени действия каждой из них, были выявлены расхождения в общем периоде
деятельности предприятия Article demonstrated research results at this stage of modern development economics approaches to
determining the duration of life cycle stages of the industrial enterprise. Systematically identified and specific
features of life cycle stages for industrial enterprises. A comparative analysis of the existing approaches to the
allocation lifecycle of the enterprise and in the presence of scientific research on the determination of the actions
of each of them, were found discrepancies in the total period of the company.
Determining the duration of life cycle stages of the industrial enterprise does not depend on the number of stages
and their names. It primarily depends on the factors influencing the activity of the enterprise (externally or
internally), as well as the specifics of the interaction of four components of the system life cycle - the industry,
businesses, products and technologies that are used by the enterprise for production. Further investigation of the
problem should be aimed at determining the specificity of factor influence on each of the stages of the life cycle
of industrial enterprise and to identify the specific features of the various combinations of the interaction of
certain components of the system life cycle of hierarchical levels.